Kajian Etnosains Proses Pembuatan Genteng sebagai Bahan Ajar Tambahan Pelajaran IPA Terpadu - Khilman Najib (Universitas PGRI Semarang, 2018)
This study aims to review the original knowledge of the community in the process of making the tile into scientific knowledge which is used as an additional teaching materials of Integrated Science lessons. The data were collected in Papringan Village, Kaliwungu District, Kudus District and Mayong Kidul Village, Mayong Sub-district, Jepara District. The research method is qualitative descriptive with data retrieval technique through observation and interview. The data obtained are then analyzed, verified, and reduced and then studied to scientific knowledge and interpreted to the concept of science in Integrated Science lesson. The results showed that the process of making tile made by the community can be interpreted into science knowledge and implemented in the learning of Integrated Science.